Perkembangan Sosial Politik dalam Tatanan Pembentukan Hukum Islam - Kurniati Kurniati (AL-Fikr, 2013)
The terms social politics and Islamic law have closely correlated meanings, which strongly support each other and even inseparable. This paper will discuss the influence of social politics development along the formation of Islamic law. Research questions to be addressed are: what is the nature of politics and power in Islam?, to what extent is the political influence on the development of Islamic law?, and what is the social history of the establishment of Islamic law? This research has a development characteristic and applies a socio-historical approach. The result indicates that the essence of politics and power is everything that leads to how to manage and organize governance in a country for the benefit of its nation on the principles of justice. With regards to political influence on the development of Islamic law, it significantly depends on the circumstances that exist in every decade.  As for the social history of the Islamic law establishment, it is divided into six phases, beginning with the phase in which everything is referred directly to the Prophet, to end up in the last phase, which is the phase of taqlid (blindly following earlier opinions from priests).